2022
DOI: 10.1021/acsami.2c08510
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogenated Boride-Assisted Gram-Scale Production of Platinum–Palladium Alloy Nanoparticles on Carbon Black for PEMFC Cathodes: A Study from a Practical Standpoint

Abstract: Platinum–palladium (PtPd) alloy catalysts with high durability are viable substituents to commercial Pt/C for proton exchange membrane fuel cells (PEMFCs). Herein, a facile approach for gram-scale preparation of Pt x Pd100–x alloy nanoparticles on carbon black is developed. The optimized Pt54Pd46/B–C catalyst shows a mass activity (MA) of 0.549 A mgPt –1 and a specific activity (SA) of 0.463 mA cm–2 at the rotating disk electrode (RDE) level, which are 3.4 and 1.9 times those of commercial Pt/C, respectively.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…Several studies have confirmed that HB sheets exhibit semimetal electronic properties, 14 superior catalytic properties, 15–19 and specific reductant properties. 17,20,21 Fujino et al demonstrated the ability of HB sheets to catalyze the production of ethylene from ethanol with high selectivity and long-term stability.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…Several studies have confirmed that HB sheets exhibit semimetal electronic properties, 14 superior catalytic properties, 15–19 and specific reductant properties. 17,20,21 Fujino et al demonstrated the ability of HB sheets to catalyze the production of ethylene from ethanol with high selectivity and long-term stability.…”
Section: Introductionmentioning
confidence: 95%
“…2 These HB sheets are predicted to exhibit intriguing physical and electronic properties, [3][4][5] making them suitable for a variety of applications including superior batteries, [6][7][8] sensors, 9 hydrogen storage materials, [10][11][12] and current limiters. 13 Several studies have confirmed that HB sheets exhibit semimetal electronic properties, 14 superior catalytic properties, [15][16][17][18][19] and specific reductant properties. 17,20,21 Fujino et al demonstrated the ability of HB sheets to catalyze the production of ethylene from ethanol with high selectivity and long-term stability.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…[35] Carbon nanotubes and graphene are examples of high graphitization materials, with improved corrosion resistance due to their perfect sp 2 structure; however, this feature can make it difficult for the firm and uniform deposition of Pt NPs due to the lack of anchorage sites. [32] As an alternative, heteroatom doping with N, [36] S [37,38] or B [39] have been used to regulate the charge redistribution of carbon and improve the interactions between Pt and carbon, which is proven to be beneficial for improving the durability of ORR catalysts. Alternatively, non-carbonaceous materials such as metal oxides and carbides have also been explored, but their limited electrical conductivity and lack of porosity could hinder their use as support.…”
Section: Introductionmentioning
confidence: 99%
“…[24] They can also reduce specific metal ions to form nanocomposites. [25][26][27][28][29] Notably, hydrogen-deficient HB sheets can adsorb CO 2 and convert it into methane and ethane, even at low temperatures (e.g., 423 K). [30] In addition, theoretical modeling and computer simulations demonstrate that HB sheets are promising candidates for certain applications, such as hydrogen-storage materials, [31][32][33][34][35] battery anode materials, [36][37][38][39] highly selective and sensitive sensors, [40,41] current limiters, [42] and photodetectors.…”
Section: Introductionmentioning
confidence: 99%